Evaluasi Kinerja Sistem Surveilans Kesehatan Masyarakat di Dinas Kesehatan Provinsi Sumatera Utara: Penelitian - Irfan Sajali; Rahmah Dwi Asti; Andwina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Public health surveillance is a crucial element of the healthcare system, enabling it to detect, analyze, and respond to disease events quickly and accurately. This study aims to evaluate the performance of the surveillance system at the North Sumatra Provincial Health Office, including human resource input, data collection, processing, and analysis, and information dissemination. The method used was descriptive qualitative through in-depth interviews and document review. The results indicate that despite adequate human resources, limited infrastructure, such as computers and transportation, remains a barrier.